Automatic docking system using sonar - Akther, Rabeya; Md. Safwan Bin Moazzem (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.